From pleasure to purchase: Exploring urban consumers' impulsive buying behavior - Purwanto, Edi; Yanti , Sania Eka (Journal of Management and Digital Business, 2024)
The study investigates the factors influencing impulsive buying among urban consumers using Shopee Live Streaming in Indonesia. Considering the rapid increase in internet users and online shopping in Indonesia, this research explores how shopping enjoyment and parasocial relationships contribute to impulsive purchases, with the urge to buy acting as a mediator. Employing a quantitative research design, data were collected from 100 respondents via a structured questionnaire and analyzed with Structural Equation Modeling (SEM) utilizing SmartPLS software. The findings reveal that shopping enjoyment and parasocial relationships significantly enhance the urge to buy, positively influencing impulsive buying. The study highlights the critical mediating role of the urge to buy in transforming shopping enjoyment and parasocial relationships into impulsive purchasing behaviors. This research provides novel insights into consumer behavior in live-streaming e-commerce platforms, offering practical implications for marketers to enhance customer engagement and impulsive buying tendencies through the strategic use of live-streaming features.